Pelatihan pengolahan buah Apel sortiran menjadi topping kue Pie untuk anggota Aisyah Kota Batu - Sri Winarsih; Bayu Etti Tri Adiyastiti; Devi Dwi Siskawardani (Unri Conference Series: Community Engagement, 2020)
The aim of this activity is to increase the knowledge and skills of Aisyah members from Batu citys in recognizing the potential and utilizing agricultural crops and livestock products to be new products that are preferred by the community. The method of implementing the activity is counseling the potential natural resources, tourism, agriculture, also increaase skill to develop its products to be new product has value added, for example pie. The participants welcomed the counseling and training activities. Based on the organoleptic test, apple pie produced get good acceptance form panelist.